Determinants of Formal and Informal Sector Labor Absorption in South Sulawesi Province - Mirwan, Sri Handila; Nurjaya, Nurjaya; Yusuf.Y.S, Muhammad; Said, Samsuardi (Formosa Journal of Science and Technology, 2024)
This research aims to determine the influence of the Human Development Index and GRDP on the absorption of formal and informal sector workers in South Sulawesi Province. This research uses multiple regression analysis and panel data, namely using cross-section and time series data in 24 regencies/cities in South Sulawesi Province with a time interval of 5 years 2019-2023. The research results obtained show that HDI has a negative and significant influence on labor absorption, with a significance value of 0.000, a t-statistic value of -4.920, and a regression coefficient value of -0.058, GRDP has a positive and significant influence on labor absorption, with The significance value is 0.000, the t-statistic value is 10,748 and the regression coefficient value is 0.610. MSMEs support the stabilization of income of people who work in the informal sector.